Accessible visual communication of climate change and its impacts on archaeological cultural heritage (PerCursos, 2021)
Attractive visual images can be a key to communicating effectively according to climate change. Far from cliché photos of melted glaciers, polar bears and chimneys, the topics in the Special Report on 1.5C (SR15) of the Intergovernmental Panel on Climate Change tell a more human and urgent story. It must be clear that the effects of these changes, whether due to anthropic influence or as part of natural cycles, are different for each geographical area and that they provoke and will provoke different forms and degrees on every aspect of life, including the assets of the archaeological cultural heritage. This research seeks to map how the strategy proposed by the Climate Visuals Program, developed and developed by Climate Research, can be adapted to the Brazilian context, promoting access to its content also for people with visual impairments. Through this first approach, there are no longer the next steps to build a digital material that makes visual communication not only attractive, but accessible, of climate change and its impacts on the Archaeological Cultural Heritage.
Keywords: audio description; cultural heritage; climate change; IPCC; visual communication